2021
DOI: 10.14202/vetworld.2021.2339-2345
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with Eimeria species infection in cattle of different geographical regions of Indonesia

Abstract: Background and Aim: Eimeria spp. are gastrointestinal protozoans that affect animal productivity, thereby causing symptoms that range from bloody diarrhea to death. These symptoms cause economic losses to farmers. The distribution of Eimeria spp. in cattle has, therefore, been reported to have spread widely, especially in the tropics and subtropics. Indonesia is a tropical country at high risk of Eimeria infections. This study aimed to identify the prevalence and risk factors related to the levels of eimeriosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
5
23
0
Order By: Relevance
“…have been available for more than 20 years. However, despite their status as the “gold standard” of detection for many diseases, conventional coccidial diagnostics have yet to be replaced [ 14 , 15 ]. The resistance of the oocyst wall to anything other than mechanical breakage, the oocyst level, restricting access to template DNA (for most infecting species), and PCR interference by the surrounding fecal material have all hindered the use of PCR in Eimerian biology [ 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…have been available for more than 20 years. However, despite their status as the “gold standard” of detection for many diseases, conventional coccidial diagnostics have yet to be replaced [ 14 , 15 ]. The resistance of the oocyst wall to anything other than mechanical breakage, the oocyst level, restricting access to template DNA (for most infecting species), and PCR interference by the surrounding fecal material have all hindered the use of PCR in Eimerian biology [ 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…oocysts, which are developed in the form of feces that is resistant to most disinfectants and environmental conditions. Parasites can survive for a long time and are a source of further infection in the environment (Lucas et al 2014;Ekawasti et al 2021). Thus, the presence of these Eimeria oocysts may indicate direct or indirect infection via the fecal-oral route.…”
Section: Discussionmentioning
confidence: 99%
“…very host-specific, and more than 20 species of Eimeria are defined in livestock (Heidari and Gharekhani 2014). Eimeria bovis and Eimeria zuernii are the most common pathogenic species in calves worldwide causing morbidity and death with impaired intestinal absorption and are often associated with diarrhea containing blood, and fibrin (Ekawasti et al 2021). Calves can be affected by stress, challenge dose, and immune status in cases of coccidiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ekawasti et al [4] reported 52.3% prevalence of Eimeria on Java Island. Furthermore, bovine coccidiosis has also been reported in Maluku Island as the highest (94.1%) prevalence, followed by Kalimantan (83%), Sumatra (70.3%), Sulawesi (68.9%), Papua (62.3%), and Nusa Tenggara (58.5%) [18]. The variation in prevalence and type of infection can differ depending on the various infection rates and shedding intensities of individuals.…”
Section: Discussionmentioning
confidence: 99%